The Impact Of Disclosure Of Leverage, Capital Intensity, Liquidity And Company Size On Tax Avoidance - Vela Tri Juliani; Fachruzzaman Fachruzzaman (UNIVED Press, 2024)
This study aims to provide empirical evidence on the influence of disclosing leverage, capital intensity, liquidity, and company size on tax avoidance. The dependent variable is tax avoidance, measured using the effective tax rate (ETR) as a proxy, while the independent variables are leverage, capital intensity, liquidity, and company size. The study used a sample of 63 mining companies listed on the Indonesia Stock Exchange from 2018 to 2022. The results of the research indicate that leverage, capital intensity, liquidity, and company size do not have an impact on tax avoidance.